2021
DOI: 10.1111/jth.15215
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of thromboembolism in patients with ALK‐ and EGFR‐mutant lung cancer: A cohort study

Abstract: Introduction Thromboembolism (TE) is common in patients with non‐small cell lung cancer (NSCLC) and is associated with worse outcomes. Recent advances in the understanding of NSCLC have led to the identification of molecular subtypes such as anaplastic lymphocyte kinase (ALK) and epidermal growth factor receptor (EGFR) mutations. The association of these subtypes with risk of TE has not been fully explored. Methods We conducted a retrospective cohort study of consecutive NSCLC patients seen at the Cleveland Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Other studies also found limited clinical value of the Khorana score in patients with lung cancer, indicating the need for considering other risk markers for this subgroup. 52,53 Indeed, refined risk stratification to guide primary prevention of venous thromboembolism remains an unmet need among cancer patients. Cancer-specific Khorana score thresholds or development of cancer-specific risk scores are needed for improving individualized risk assessment, while also considering patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found limited clinical value of the Khorana score in patients with lung cancer, indicating the need for considering other risk markers for this subgroup. 52,53 Indeed, refined risk stratification to guide primary prevention of venous thromboembolism remains an unmet need among cancer patients. Cancer-specific Khorana score thresholds or development of cancer-specific risk scores are needed for improving individualized risk assessment, while also considering patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogenic signaling and the presence of a stressful microenvironment, as is commonly found in human tumors, regulate the expression of F3 [120,121]. Some of the somatic mutations that play a driver role in tumor progression, such as those found in MET or RAS, might directly regulate F3 expression [122,123]. Genomic instability also directly regulates F3 expression, as described by Bakhoum et al who identified F3 as a transcriptional target of NF-kB activated by the innate immune mechanisms sensing cytosolic DNA, cGAS-STING [124].…”
Section: Toward a Systems-level Understanding Of The Tumor Coagulomementioning
confidence: 99%
“…The Khorana score was not a useful tool to predict thrombosis in our mostly HR + HER2 negative breast cancer population while on CDK4/6 inhibitors. Increasingly, the role of the tumor mutational profile as an independent predictor of cancer‐associated thrombosis is being described 29‐32 . For example, non‐small cell lung cancers (NSCLCs) driven by aberrant anaplastic lymphoma kinase (ALK) rearrangements have been shown to be at increased risk for arterial and venous thrombosis compared to non‐ALK rearranged NSCLC 29,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, the role of the tumor mutational profile as an independent predictor of cancer‐associated thrombosis is being described 29‐32 . For example, non‐small cell lung cancers (NSCLCs) driven by aberrant anaplastic lymphoma kinase (ALK) rearrangements have been shown to be at increased risk for arterial and venous thrombosis compared to non‐ALK rearranged NSCLC 29,31 . Another recent publication that evaluated over 14 000 pooled solid tumor samples, including 14% from breast tumors, identified seven somatic tumor mutations independently associated with VTE risk.…”
Section: Discussionmentioning
confidence: 99%